Numerical study on rotor tip flow loss in a boundary layer ingesting fan under different operating conditions. (April 2023) - Lu, Hanan; Yang, Zhe; Pan, Tianyu; Li, Qiushi
As a key component of boundary layer ingesting (BLI) propulsion system, the BLI fan operates permanently at an inflow distortion condition and the distortion-induced aerodynamic loss in the fan would seriously in turn discount the aerodynamic benefit achievements of BLI propulsion system. Moreover, as the fan rotor rotates along the annulus, the blade tip region will encounter the greatest distortion intensity and operating condition variation, thus contributing to major loss source in the BLI fan rotor. To explore the loss mechanisms in rotor blade tip region of a BLI fan, numerical investigations are conducted to study the influences of BLI inflow distortion on the flow loss in the fan rotor blade tip region at different mass flow working conditions. The results indicate that the flow loss in blade tip region increases notably from near choke to near stall condition, accounting for about 38%–51% of total aerodynamic loss in the BLI fan rotor. The loss in the tip region reaches the maximum at 240° circumferential location where the rotor blade is leaving the distortion region along the annulus because high local blade load and maximum relative Mach number are presented. In the meanwhile, as the rotor blade load increases from near choke to near stall condition, the shock structure in the blade passage varies and the interaction between shock and tip leakage flow is also intensified because of enhanced local leakage flow and forward displacement of shock. At near peak efficiency and near stall conditions, the interaction between the leakage vortex and shock in the tip region is notably intensified at 240° circumferential location and the local leakage vortex expands rapidly after the shock, leading to a vortex breakdown. The resultant flow blockage at 240° circumferential location is much higher than those at other annulus locations and the maximum blockage has increased from 18% to 42% from near choke to near stall condition, contributing fundamentally to the additional loss in the BLI fan. At the same time, by further quantifying local aerodynamic loss, it is also found that the leakage flow loss due to interaction between leakage flow and shock is the major source of loss in the BLI fan rotor, and the vortex breakdown at high blade load condition (from peak efficiency to near stall condition) could even lead to an increment of loss with a slop about three times of that at low blade load condition (near choke condition).